"Chicken Is Not a Bird - Kirkenes Is Not Abroad": Borders and Territories in the Perception of the Population in a Russian-Norwegian Borderland - Rogova, Anastasia (Umeå University Library, 2009)
This article focuses on the Russian-Norwegian borderland and its development in the 1990s and early twenty-first century. In 1991, with the collapse of the Soviet Union, the border was opened for communication in both ways, and since then its meaning has undergone significant changes that have reshaped the whole territory. My argument is that there are nowadays a considerable number of people in the borderland whose “own” territory is not limited any more by the state border, but includes both Russian and Norwegian territories as parts of a unified personal space, which is neither Russia, nor Norway to the full extent. Practical, operative space has expanded for the local people who actively use border-related resources in their everyday life. Local identity has changed, and the broadening of operative space has led to the formation of new life strategies and social mobility in the region. The idea of a unified crossborder space is now implemented both on the individual level, as a result of extensive cross-border contacts, and on the level of political and administrative decisions and official discourses. Furthermore, political and cultural elites of the region are actively constructing the concept of the Euro-Arctic Barents Region as an identity region.